Update on tick-borne pathogens detection methods within ticks - Krupa, Eva; Dziedziech, Alexis; Paul, Richard; Bonnet, Sarah (Current research in parasitology & vector-borne diseases, 2024)
Ticks are known vectors of various pathogens, including bacteria, parasites and viruses, that impact both animal and human health. Improving knowledge of the distribution of tick-borne pathogens, combined with their early detection in ticks, are essential steps to fight against tick-borne diseases and mitigate their impacts. Here we give an overview of what are the common methods of pathogen detection in tick samples, including recent developments concerning how to handle tick samples, get access to tick-borne pathogens by chemical or physical disruption of the ticks, and methods used for the RNA/DNA extraction steps. Furthermore, we discuss promising tools that are developed for other sample types such as serum or blood to detect tick-borne pathogens, and those that could be used in the future for tick samples. [Display omitted] •Review of optimal storage conditions, cleaning steps, and nucleic acid extraction of pathogens in tick samples.•Review of the state-of-the-art of molecular diagnostics for tick-borne pathogen detection in tick samples.•Promising tools for use in field settings, especially in resource-limited sites.